Dietary factors and onset of natural menopause: A systematic review and meta-analysis. (May 2022) - Grisotto, Giorgia; Farago, Julian S.; Taneri, Petek E.; Wehrli, Faina; Roa-Díaz, Zayne M.; Minder, Beatrice; Glisic, Marija; Gonzalez-Jaramillo, Valentina; Voortman, Trudy; Marques-Vidal, Pedro; Franco, Oscar H.; Muka, Taulant
Highlights: Higher intake of green and yellow vegetables was associated with earlier age of onset of natural menopause. High intakes of some dairy products, such as low-fat and skimmed milk, were associated with a later onset of natural menopause. A low intake of alcohol was associated with a later onset of natural menopause. A vegetarian diet could be associated with early onset of natural menopause. Abstract: Background: Diet has been suggested to play a role in determining the age at natural menopause; however, the evidence is inconsistent. Objective: We systematically reviewed and evaluated published research about associations between diet and onset of natural menopause (ONM). Methods: We searched 6 databases (Medline, Embase, Cochrane, PubMed, Web of Science and Google Scholar) through January 21, 2021 to identify prospective studies assessing the association between diet and ONM. Two independent reviewers extracted data using a predesigned data-collection form. Pooled hazard risks (HRs) were calculated using random effect models. Results: Of the 6, 137 eligible references we reviewed, we included 15 articles in our final analysis. Those 15 articles included 91, 554 women out of 298, 413 who experienced natural menopause during follow-up. Overall, there were 89 food groups investigated, 38 macronutrients and micronutrients, and 6 dietary patterns. Among the food groups, higher intake of green and yellow vegetables was associated with earlier age of ONM, while high intakes of some dairy products, such as low-fat, skimmed milk, and low intake of alcohol were associated with a later onset. We observed no consistent association between macronutrient and micronutrient intake and ONM. Our results suggests that a vegetarian diet could be associated with early ONM; we did not observe any other consistent effect from other dietary patterns. Limitations included the number of studies, lack of replication studies and the research being of an observational nature; most studies (11/15) were at medium risk of bias. Conclusion: Although some food items were associated with ONM, the overall evidence about associations between diet and ONM remains controversial. Prospero id: CRD42021232087